Economic Analysis of Pre and Postpartum Alphatocopherol Supplementation for Milk Performance and Dry Matter Intake of Dairy Cows in Tropical Region - Singh, Amit Kumar; Bhakat, Champak; Mohammad, Asif; Chatterjee, Anupam; Karunakaran, Muthupalani; Ghosh, Monoj Kumar (International Journal of Livestock Research, 2020)
Proper management during transition period and initial lactation period is crucial for overall lactation production performances of dairy animals. Alphatocopherol (Vitamin E) supplementation has showed better results in dairy cows as expressed in different studies. This experiment was done to see the effect of pre and postpartum Alphatocopherol supplementation for Jersey crossbred cows @ 1g/day/cow. Survey was conducted on a total of 191 respondents and out of which 19 suitable and healthy animals were selected for this experiment. Suitable 19 healthy milch Jersey crossbred cows which were separated into three comparable groups viz. control, T1 and T2. Treatment groups viz. T1 (n=7), T2 (n=6) were supplemented with Alphatocopherol as compared to control group C (n=6) during dry period and initial lactation period respectively. Statistically analyzed data showed significantly no difference (P>0.05) dry matter intake during dry period and during initial 60 days of lactation period. Economic analysis was done to access the efficiency of utilizing Alphatocopherol during dry and initial lactation period in dairy cows of tropical region. Profit earned as a result of Alphatocopherol in T1 group was 2.36 times and 2.88 times more in T2 group animals as compared to control group animals. In conclusion it can be stated that the supplementation of Alphatocopherol can improve the production performance of dairy cows economically during initial lactation period of dairy cows at tropical region.